2008
DOI: 10.1002/mma.1060
|View full text |Cite
|
Sign up to set email alerts
|

Charged relativistic spheres with generalized potentials

Abstract: A new class of exact solutions of the Einstein-Maxwell system is found in closed form. This is achieved by choosing a generalised form for one of the gravitational potentials and a particular form for the electric field intensity. For specific values of the parameters it is possible to write the new series solutions in terms of elementary functions. We regain well known physically reasonable models. A physical analysis indicates that the model may be used to describe a charged sphere. The influence of the elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…3, we have plotted the anisotropy parameter such that (0) = 0 as P t and P r are equal at center, which is desirable physical condition described by Bowers and Liang [39] and Ivanov [40]. For η = sess the opposite behavior which is similar to Thirukkanesh and Maharaj [10]. Figure 4 depicts the behavior of speed of sound d P r dρ which satisfies the casuality condition explained by Delgaty [1].…”
Section: Physical Analysismentioning
confidence: 75%
See 2 more Smart Citations
“…3, we have plotted the anisotropy parameter such that (0) = 0 as P t and P r are equal at center, which is desirable physical condition described by Bowers and Liang [39] and Ivanov [40]. For η = sess the opposite behavior which is similar to Thirukkanesh and Maharaj [10]. Figure 4 depicts the behavior of speed of sound d P r dρ which satisfies the casuality condition explained by Delgaty [1].…”
Section: Physical Analysismentioning
confidence: 75%
“…The equivalent form of Eqs. (9)- (16), with linear EoS, was analyzed by Thirukanesh and Maharaj [10] and with quadratic EoS by Feroze and Siddiqui [17] as well as by Maharaj and Takisa [18]. Also, Takisa and Maharaj [26] dealt it with polytropic EoS.…”
Section: The Fundamental Anisotropic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirukkanesh and Maharaj [16] generated a new class of solutions in closed form using a systematic series analysis. This approach generates a number of difference equations which must be solved explicitly from first principles.…”
Section: Introductionmentioning
confidence: 99%
“…Di Prisco et al [15] explored the effect of charge on the relation between the Weyl tensor and the inhomogeneity of energy density and concluded that Coulomb repulsion might prevent the gravitational collapse of the sphere. Thirukkanesh and Maharaj [16] investigated that gravitational attraction is compensated by the Coulomb's repulsive force along with gradient pressure in a gravitational collapse. Sharif and Abbas [17] discussed the effect of electromagnetic field on spherically symmetric gravitational collapse with cosmological constant.…”
Section: Introductionmentioning
confidence: 99%